(untitled) (Revista cientifica In Vestigium Ire, 2021)
Business stability as an integrating concept of economic growth, management of business culture, leadership, recognition of human capital capabilities, was until 2019 an obsession for entrepreneurs around the world. All directed their efforts to make the company sustain itself in an operational cycle recorded from economic theory. However, with the arrival of the COVID-19 pandemic, growth engines stopped, consumption and investment were disrupted that made it difficult for companies to stay in the market. Many could not handle the losses and gave in to the struggle to survive. In this context, the article develops a descriptive review of business stability factors as a resource for small and medium-sized companies in the city of Neiva to overcome the crisis by avoiding their disappearance.